Popularity of Tourist Attraction in Bali From the Perspective of Foreign Tourists - Sudiarta, I Nyoman (E-Journal of Tourism; Volume 2 Number 2 (September 2015), 2015)
This study aims to determine the popularity of tourist attraction in Bali, the position of a tourist attraction in Bali Respondents in this study were foreign tourists visiting Bali, the number of samples taken by 100 respondents by purposive sampling. Analysis of data using descriptive and statistical analysis of multidimensional scaling. The most popular attraction by tourists are Kuta, Sanur, Nusa Dua, Jimbaran, Tanah Lot and Ubud. Group tourist attraction in Bali positioned into four quadrant and two-dimensional. Dimension 1  is the tourist attractions that have many similarity or close competitors and dimension  2  is illustrates  attraction that has a lot of differences or distant competitors.
Keywords: position, attraction, Bali, foreign tourist, multidimensional scaling analysis